Pretreatment of Adipose Derived Stem Cells with Curcumin Facilitates Myocardial Recovery via Antiapoptosis and Angiogenesis - Jianfeng Liu; Ping Zhu; Peng Song; Weiping Xiong; Haixu Chen; Wenhui Peng; Shuxia Wang; Shan Li; Zhiqing Fu; Yutang Wang; Haibin Wang (Stem Cells International)
The poor survival rate of transplanted stem cells in ischemic myocardium has limited their therapeutic efficacy. Curcumin has potent antioxidant property. This study investigates whether prior curcumin treatment protects stem cells from oxidative stress injury and improves myocardial recovery following cells transplantation. Autologous Sprague-Dawley rat adipose derived mesenchymal stem cells (ADSCs) were pretreated with or without curcumin. The hydrogen peroxide/serum deprivation (H2O2/SD) medium was used to mimic the ischemic condition in vitro. Cytoprotective effects of curcumin on ADSCs were evaluated. Curcumin pretreatment significantly increased cell viability and VEGF secretion, and decreased cell injury and apoptosis via regulation of PTEN/Akt/p53 and HO-1 signal proteins expression. The therapeutic potential of ADSCs implantation was investigated in myocardial ischemia-reperfusion injury (IRI) model. Transplantation of curcumin pretreated ADSCs not only resulted in better heart function, higher cells retention, and smaller infarct size, but also decreased myocardial apoptosis, promoted neovascularization, and increased VEGF level in ischemic myocardium. Together, priming of ADSCs with curcumin improved tolerance to oxidative stress injury and resulted in enhancement of their therapeutic potential of ADSCs for myocardial repair. Curcumin pretreatment is a promising adjuvant strategy for stem cells transplantation in myocardial restoration.